The morphological and agronomic characters of five fiber mutants - JIANG Shu-li; WANG Xue-de (浙江大学学报. 农业与生命科学版, 2001)
Five fiber mutants in upland cotton were compared to each other or with TM-1 in morphogenesis and agronomic character. The results showed that protuberance of fiber cells from TM-1 ovule was first appeared at the funiculus crest, then spread from the chalazal cap to the micropylar, this situation was also observed in mutants with fiber or fuzz, such as Naked seed (N1) and Ligon lintless (Li). Seed of Li mutant had no long fibers, only covered with fuzz and short fibers, of which short fibers were protruded from ovule at the day of flowering (0 DPA, DPA: Days Post-Anthesis) and fuzz at 5 DPA. Fuzzless mutant, also called as naked seed (N1), had only long fibers, protuberance of its long fiber cells was first seen at 0 DPA, but could be continued to 1 DPA. Lint yield of fiber mutant was lower since lint percentage or lint index was lower than normal-type cotton TM-1, some of other traits, such as higher seed index, better fiber quality.